Altering the Agenda, Shifting the Strategy: The Grundfest of 1571 as Philippist Program for Lutheran Concord - Kolb, Robert (The sixteenth century journal, 1999)
After two decades of trying to avoid controversy in spite of heavy criticism of their public teaching, the "Philippist" theologians of electoral Saxony began a barrage of accusations against what they considered heretical positions among their Lutheran opponents, all of whom they labeled "Flacians." Centerpiece of this counterattack was the Grundfest of 1571, a detailed defense of Philippist Christology and attack on the positions of foes, particularly Martin Chemnitz and Jakob Andreae. This document redefined the field of controversy among Late Reformation Lutherans and thus determined much of the agenda treated by Chemnitz, Andreae, and their colleagues in the composition of the Formula of Concord of 1577.